Prospectively ECG-triggered high-pitch coronary angiography with third-generation dual-source CT at 70 kVp tube voltage: Feasibility, image quality, radiation dose, and effect of iterative reconstruction - Hell, Michaela M.; Bittner, Daniel; Schuhbaeck, Annika; Muschiol, Gerd; Brand, Michael; Lell, Michael; Uder, Michael; Achenbach, Stephan; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2014)
Low tube voltage reduces radiation exposure in coronary CT angiography (CTA). Using 70 kVp tube potential has so far not been possible because CT systems were unable to provide sufficiently high tube current with low voltage.We evaluated feasibility, image quality (IQ), and radiation dose of coronary CTA using a third-generation dual-source CT system capable of producing 450 mAs tube current at 70 kVp tube voltage.Coronary CTA was performed in 26 consecutive patients with suspected coronary artery disease, selected for body weight <100 kg and heart rate <60 beats/min. High-pitch spiral acquisition was used. Filtered back projection (FBP) and iterative reconstruction (IR) algorithms were applied. IQ was assessed using a 4-point rating scale (1 = excellent, 4 = nondiagnostic) and objective parameters.Mean age was 62 ± 9 years (46% males; mean body mass index, 27.7 ± 3.8 kg/m(2); mean heart rate, 54 ± 5 beats/min). Mean dose-length product was 20.6 ± 1.9 mGy × cm; mean estimated effective radiation dose was 0.3 ± 0.03 mSv. Diagnostic IQ was found in 365 of 367 (FBP) and 366 of 367 (IR) segments (P nonsignificant). IQ was rated "excellent" in 53% (FBP) and 86% (IR) segments (P = .001) and "nondiagnostic" in 2 (FBP) and 1 segment (IR) (P nonsignificant). Mean IQ score was lesser in FBP vs IR (1.5 ± 0.4 vs 1.1 ± 0.2; P < .001). Image noise was lower in IR vs FBP (60 ± 10 HU vs 74 ± 8 HU; P < .001).In patients <100 kg and with a regular heart rate <60 beats/min, third-generation dual-source CT using high-pitch spiral acquisition and 70 kVp tube voltage is feasible and provides both robust IQ and very low radiation exposure.
EVALuna2:11954